(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
This article aims to present the memories of the authors on the development of behavior analysis in their respective states: Maranhão, Ceará and Bahia. It is noteworthy that the teaching of this discipline comes along with the formation of the first psychology departments in public universities. The development of groups interested in study and research, and regional and national events also contributed decisively to the spread of knowledge and technology of behavior analysis. The text also includes notes on the present day and possible glimpses into the future